Evaluation of the quality of meat and carcasses from sheep fed diets containing three types of oils - Costa, Thays Syntya Antunes da; Silva, Jamile Andréa Rodrigues da; Faturi, Cristian; Silva, André Guimarães Maciel e; do Rêgo, Aníbal Coutinho; Monteiro, Edwana Mara M.; Budel, Juliana Cristina de Castro; Castro, Vinícius Costa Gomes de; Barbosa, Antônio Vinicius Corrêa; Silva, Welligton Conceição da; Lourenço-Junior, José de Brito (Frontiers in Veterinary Science, 2023)
The objective of this research was to evaluate the quantitative and qualitative characteristics of the carcass and meat of lambs fed with different types of oil. Thirty male, uncastrated, mixed breed (Santa Inês × Dorper) sheep were used in this experiment and were distributed in random blocks with three treatments and ten repetitions per treatment where each animal represents a replicated experimental unit. The three treatments were the following experimental diets: soybean oil in natura; soybean oil after use in frying; and palm oil (Elaeis guineensis). Oils were incorporated to the sheep’s diet at a 4% level of incorporation. The carcasses were evaluated for their hot and cold yields, loss due to cooling, finish, conformation, internal fat concentration, morphometric measurements, tissue composition, and commercial cuts. The addition of soybean oil in natura, residual soybean oil from frying, and palm oil to the lamb´s diet did not alter any of the evaluated characteristics, which therefore can be interpreted as favoring the use of any of these three oils as a supplement to their diet, and the three oils imparted good characteristics to the carcasses and the meat.